The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1166/jnn.2016.10890
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tm3+ Concentration and Temperature on Blue and NIR Upconversion Luminescence in Tm3+/Yb3+ Co-Doped NaY(WO4)2 Microstructures

Abstract: Tm³⁺/Yb³⁺ codoped NaY(WO₄)₂ microstructures with various Tm³⁺ concentrations and 10 mol% Yb³⁺ concentration were prepared by a microwave-assisted hydrothermal method, and their upconversion luminescence (UCL) was investigated. Under excitation at 980 nm, Tm³⁺/Yb³⁺ codoped NaY(WO₄)₂ exhibited strong blue and near infrared (NIR) emissions, respectively, corresponding to ¹G₄ --> ³H₆ and ³H₄ --> ³H₆ transitions, with weak red emission due to the ¹G₄ --> ³H₄ transition. The optimum doping concentrations of Tm³⁺ for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Rare‐earth vanadate matrices REVO 4 were co‐doped with the pairs of lanthanide ions: 20% Yb 3+ and 1% Ho 3+ , 20% Yb 3+ and 1% Er 3+ , and 20% Yb 3+ and 0.5% Tm 3+ . Concentrations were chosen on the basis of literature and are known to usually provide effective up‐conversion luminescence …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rare‐earth vanadate matrices REVO 4 were co‐doped with the pairs of lanthanide ions: 20% Yb 3+ and 1% Ho 3+ , 20% Yb 3+ and 1% Er 3+ , and 20% Yb 3+ and 0.5% Tm 3+ . Concentrations were chosen on the basis of literature and are known to usually provide effective up‐conversion luminescence …”
Section: Methodsmentioning
confidence: 99%
“…Concentrations were chosen on the basis of literature and are known to usually provide effective up-conversion luminescence. [45][46][47] (2) Apparatus The physicochemical properties of the prepared compounds were studied with the use of X-ray diffraction analysis (XRD), energy-dispersive X-ray spectroscopy (EDX), transmission electron microscopy (TEM), and spectroscopic measurements: excitation and emission spectra, luminescence decays, dependence between the intensity of luminescence and energy of the laser as an excitation source.…”
Section: Methodsmentioning
confidence: 99%
“…Then, a problem arises as to what is the optimal concentration of REEs to be doped, which is interesting for researchers and many studies have focused on investigating the influence of the REE concentration on crystal optical properties like up-conversion efficiency. 8–11 It was found that the transmission and emission spectra, up-conversion efficiency and some other optical properties are dependent on the doped REE concentration. From this perspective, accurate determination of the REE concentration in NaLn(WO 4 ) 2 laser crystals is of vital importance for quality control of these crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Yb 3+ -Tm 3+ co-doped materials were more efficient candidates for NIR-to-NIR UC luminescence and were significant light sources for biologically non-destructive detection. In the past decades, a large number of investigations about Yb 3+ -Tm 3+ co-doped UC materials have been widely reported for achieving high-efficiency NIR UC luminescence [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%